Packaging Influences towards Consumers’ Purchasing Decision - Lee, Looi Roong (2012)
This paper is to investigate the effect of packaging influences towards the consumers’ purchasing decision. As the environment is changing and the quality of lifestyle is improving, consumers tend to purchase products not only based on the basic requirements but they also look into the packaging of the products. Companies in the industry need to take into more considerations when producing products such as the aspects of packaging of the products, they need to put more effort on designing the packaging of the products besides just focusing only on the quality of the products itself in order to attract more consumers’ attention. Packaging of the products could play greater role than just the basic function of itself. There are a few of research being done in this area showed that packaging is not the just function merely as the container of the products but it also plays an important part in affecting the consumers’ purchasing decision. It could help in providing differentiation between other similar products on the shelf and enhance the purchasing decisions of consumers through the different appealing of packaging design. This paper will look into the aspects of packaging such as the visual impact or attractiveness of the products, type of packaging material, front-of-pack labeling and nutrition information of the products and determine the influential effect of these aspects towards the consumers’ purchasing decisions. Quantitative survey will be conducted on the areas such as Kuala Lumpur and Selangor with the sample size of 200. Data being collected will be analyzed through software of SPSS version 17.